Suspected heparin-resistant contact activation during membrane-based therapeutic plasma exchange: a case report - Atsuto Niwa; Sanae Kikuchi; Yuki Nakai; Ayumi Tomoi; Akinori Kitamura; Jun Matsuoka; Norihiko Tanimoto; Miyuki Nakano; Yoshiki Okuno; Mitsuaki Oki; Shinpei Nogami; Masaomi Sato; et al. (Renal Replacement Therapy, 2026)
Abstract Background Therapeutic plasma exchange (TPE) is recommended for steroid-refractory acute optic neuritis associated with aquaporin-4 (AQP4)-IgG-positive neuromyelitis optica spectrum disorder. However, clotting-related events in the extracorporeal circuit can interrupt treatment and jeopardize timely completion of the planned TPE course. Case presentation A 42-year-old woman presented with rapidly progressive bilateral optic neuritis, with no light perception in the right eye and finger count vision in the left eye. After intravenous methylprednisolone on hospital days 1–3, membrane-based TPE with fresh frozen plasma replacement and systemic unfractionated heparin was initiated on hospital day 4. Despite escalation of heparin, prolongation of activated partial thromboplastin time and activated clotting time remained modest. During the first session, the circuit required three normal saline rinses because of flow limitation, and white clot-like material was visually observed in the membrane and chamber. The circuit events prompted a decision not to repeat membrane-based TPE under the same conditions. The serum AQP4-IgG result became available later that same day, after completion of session 1; the positive result reinforced the need to avoid delaying completion of the planned TPE course. The subsequent three sessions were performed using centrifugal TPE with Spectra Optia® under regional citrate anticoagulation using acid citrate dextrose solution A (ACD-A). These sessions were completed without circuit instability, and decimal visual acuity improved to approximately 1.0 in both eyes by completion of the four-session treatment course. The patient was diagnosed with AQP4-IgG-positive neuromyelitis optica spectrum disorder. Conclusions When white clot-like material and recurrent flow limitation are encountered during heparin-anticoagulated membrane-based TPE, early reassessment of the anticoagulation strategy and, when necessary, a switch in TPE modality may help ensure treatment completion. Because both the TPE modality and anticoagulation method were changed simultaneously, their relative contributions to circuit stabilization could not be determined.